PENGARUH INVESTASI DAN PENGEMBANGAN SEKTOR-SEKTOR EKONOMI SERTA UMKM TERHADAP KESEMPATAN KERJA DI SUMATERA BARAT - Hendry Muhammad Ali; Herry Wira Wibawa; Atik Budi Paryanti (SMART Management Journal, 2021)
The problems studied are government and private investment as well as the development of economic sectors and MSMEs (Micro, Small and Medium Enterprises) and their effect on job opportunities in West Sumatra. The basic social problems faced in Indonesia are high levels of unemployment and poverty in the midst of government policies that have not met expectations. This study aims to analyze the effectiveness and ability to realize the targets of government policies in government and private investment, development of economic sectors, and MSMEs in order to increase job opportunities in West Sumatra Province. The factors studied are government investment, private investment, GRDP of the primary, secondary, tertiary, and MSME sectors. This study uses an explanatory method with a hypothesis testing study approach which explains the causal relationship in employment opportunities in West Sumatra through hypothesis testing. The data is compiled in time-series for the years 2000-2014 in a semi- annual period. The research model is formulated as a linear function based on Nerlove's Partial Adjustment Model approach and analyzed recursively using linear regression using the Ordinary Least Square (OLS) method. The research findings are: Government policies in public and private investment as well as the development of economic sectors and MSMEs are jointly effective in encouraging increased employment opportunities in West Sumatra. Individually, Employment Opportunities are more determined by government policies in government investment and the development of the primary and tertiary sectors. However, the government's ability to realize the target of job opportunities is still relatively low.